Semiotic construction of Islamic meaning in the lyrics of “Islamic World” by Kagamine Rin - Lubis, Muhammad Nasar; Wirman, Wirman (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2026)
This study investigates the semiotic construction of Islamic meaning in the lyrics of “Islamic World” performed by Kagamine Rin within the context of Japanese digital popular culture. As Islamic historical and religious symbols increasingly circulate in transnational media environments, their meanings are no longer transmitted solely through theological institutions but through aesthetic mediation. This research aims to examine how Islamic civilizational narratives are symbolically reconstructed in the song and how these representations function within contemporary digital culture. Employing a qualitative semiotic textual analysis supported by library research, the study integrates Stuart Hall’s theory of representation, Charles Sanders Peirce’s triadic model of the sign, and Roland Barthes’s framework of denotation and connotation. The corpus consists of the official lyrics analyzed through systematic coding of Islamic signifiers, including historical figures, theological terminology, civilizational references, and metaphorical clusters such as light, journey, leadership, and unity. The findings reveal that Islamic meaning is constructed through symbolic condensation and narrative recombination, transforming prophetic figures and historical references into ethical archetypes accessible within database-style digital aesthetics. Denotatively, the lyrics refer to Islamic history; connotatively, they construct Islam as a dynamic moral civilization characterized by knowledge, justice, expansion, and spiritual perseverance. Rather than reducing theology, the song performs symbolic relocation, recontextualizing Islamic civilizational memory within a globalized pop-cultural soundscape. The study concludes that religious symbolism in digital media can preserve moral substance while undergoing aesthetic reconfiguration, demonstrating that Islam in this context functions as a culturally adaptive ethical narrative rather than doctrinal exposition.   Penelitian ini mengkaji konstruksi semiotik makna Islam dalam lirik lagu “Islamic World” yang dibawakan oleh Kagamine Rin dalam konteks budaya populer digital Jepang. Seiring dengan semakin luasnya sirkulasi simbol-simbol historis dan religius Islam dalam lingkungan media transnasional, maknanya tidak lagi ditransmisikan semata-mata melalui institusi teologis, melainkan dimediasi secara estetis. Penelitian ini bertujuan untuk menganalisis bagaimana narasi peradaban Islam direkonstruksi secara simbolik dalam lagu tersebut serta bagaimana representasi tersebut berfungsi dalam budaya digital kontemporer. Penelitian ini menggunakan analisis tekstual semiotik kualitatif yang didukung oleh studi kepustakaan dengan mengintegrasikan teori representasi Stuart Hall, model triadik tanda Charles Sanders Peirce, serta kerangka denotasi dan konotasi Roland Barthes. Korpus penelitian berupa lirik resmi lagu yang dianalisis melalui proses pengodean sistematis terhadap penanda-penanda Islam, meliputi tokoh sejarah, terminologi teologis, referensi peradaban, serta klaster metaforis seperti cahaya, perjalanan, kepemimpinan, dan persatuan. Hasil penelitian menunjukkan bahwa makna Islam dikonstruksi melalui kondensasi simbolik dan rekombinasi naratif yang mentransformasikan figur-figur kenabian dan referensi historis menjadi arketipe etis yang dapat diakses dalam estetika digital bergaya database. Secara denotatif, lirik merujuk pada sejarah Islam; secara konotatif, lirik tersebut membangun Islam sebagai peradaban moral yang dinamis yang ditandai oleh pengetahuan, keadilan, ekspansi, dan keteguhan spiritual. Lagu ini tidak mereduksi teologi, melainkan melakukan relokasi simbolik dengan merekontekstualisasikan memori peradaban Islam dalam lanskap budaya pop global. Penelitian ini menyimpulkan bahwa simbolisme religius dalam media digital dapat mempertahankan substansi moral sekaligus mengalami rekonfigurasi estetis, sehingga Islam dalam konteks ini berfungsi sebagai narasi etis yang adaptif secara kultural, bukan sekadar eksposisi doktrinal.